2015
DOI: 10.3109/08830185.2015.1087519
|View full text |Cite
|
Sign up to set email alerts
|

STAT1 and IRF8 in Vascular Inflammation and Cardiovascular Disease: Diagnostic and Therapeutic Potential

Abstract: Inflammation importantly contributes to the pathophysiology of Cardiovascular Disease (CVD). Signal Transducer and Activator of Transcription (STAT)1 operates at the frontier of innate and adaptive immunity and its involvement in CVD has been widely appreciated. A unique role of STAT1 in cross-talk between the pro-inflammatory cytokine IFNγ and TLR4 activators (TLR4-A) has been uncovered in immune as well as vascular cells increasing inflammation. Interferon Regulatory Factor (IRF)8 whose expression was initia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 124 publications
0
31
0
Order By: Relevance
“…For example, Irf8 participates in the transcriptional regulation of TLR4 signaling in murine lung during endotoxemia (56). Irf8 and Stat1 have been shown to mediate the cross-talk between LPS-induced TLR4 signaling and the IFN-g response; both are key processes contributing to the early stages of atherosclerosis and plaque development (48). Furthermore, Irf8-regulated Ccl5, Isg15, Cd274, Oasl2, Slc15a3, and Gbp2 expression was previously found to drive the pathological inflammation during cerebral malaria (80).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Irf8 participates in the transcriptional regulation of TLR4 signaling in murine lung during endotoxemia (56). Irf8 and Stat1 have been shown to mediate the cross-talk between LPS-induced TLR4 signaling and the IFN-g response; both are key processes contributing to the early stages of atherosclerosis and plaque development (48). Furthermore, Irf8-regulated Ccl5, Isg15, Cd274, Oasl2, Slc15a3, and Gbp2 expression was previously found to drive the pathological inflammation during cerebral malaria (80).…”
Section: Discussionmentioning
confidence: 99%
“…Irf8 is a transcription factor that is restricted primarily to hematopoietic cells and often acts by associating with other transcription factors to modulate key inflammatory responses, including the IFN-g response, TLR signaling, and the expression of inducible NO synthase (48,49). When comparing PMA and IDR-1002 combined treatment with PMA challenge, Irf8 was identified to be one of the central hubs in the zero-order protein-protein interaction network, interacting with 28 other transcriptionally dysregulated proteins (27 of which were upregulated by PMA and suppressed in the presence of IDR-1002 treatment) ( Fig.…”
Section: Idr-1002 Dampened Inflammation By Suppressing An Irf8regulatmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that STAT1 and STAT5, the downstream molecules of IFN-γ, are also likely to be implicated in inflammation (Chmielewski et al, 2015; Li X. et al, 2015). Akt functions as emerging crucial regulator of multiple cellular processes, such as apoptosis, differentiation, survival, etc., (Piao et al, 2015).…”
Section: Pharmacodynamic Levelmentioning
confidence: 99%
“…Understanding the disruption of molecular mechanisms responsible for regulating these inflammatory processes may provide useful insights into CAD pathogenesis. The JAK/STAT signaling is among the most important regulatory pathways governing several inflammatory processes through the initiation of innate and adaptive immunity and mediation of divers cytokine signaling pathways . STAT1 is a member of STAT transcription factors family which transduce cytokine signaling to the nucleus following tyrosine phosphorylation/activation by JAK proteins and it is believed to be relevant to the pathogenesis of cardiovascular diseases .…”
Section: Introductionmentioning
confidence: 99%